Ternatus, a new spider genus from China with a cladistic analysis and comments on its phylogenetic placement (Araneae: Linyphiidae) - Sun, Ning; Li, Bin; Tu, Lihong (Zootaxa, 2012)
A new spider genus, Ternatus n. gen., is erected to accommodate two new erigonine species from China, Ternatus malleatusn. sp. and Ternatus siculus n. sp. Descriptions and illustrations of the new genus and new species are provided. To test the phy-logenetic placement within Linyphiidae, morphological data of the two new species were added to the matrices of two previousstudies addressing the higher level phylogeny of erigonine spiders. The results of the cladistic analyses support the monophyly of the new genus and its sister group relationship to the genus Gonatium Menge, 1868.